Evaluation of carbon dioxide absorption capacity and biomass accumulation of sub-urban plants in Universiti Tun Hussein Onn Malaysia (UTHM) - Audu, Yunusu (2018)
Carbon dioxide (CO2), is an important greenhouse gas which plays a vital role in the Earth's carbon cycle. Its continuous increase above the ambient concentration leads to global warming. The localized increase in CO2 emission in UTHM is due to a large number of automobiles and other greenhouse gases released from building facilities and nearby industries. A study was carried out on the common species of trees, shrubs, palms, herbaceous and bamboos planted within the campus to estimate the amount of CO2 sequestered. Estimation of carbon storage of studied species was obtained through assessments of standing biomass as well as measurement of their photosynthetic capacity. Data for A/Ci and AQ analysis was collected and the curve are fitted based on a nonrectangular hyperbola model. Results obtained indicates that tree species Spathodea campanulata recorded a high CO2 absorption of 14.40 μmol m-2 s-1. In shrub category, Sanchezia speciosa was found to have a high CO2 absorption capacity of 15.37 μmol m-2 s-1, while Palm Roystonea regia performed above others in their group, but Musa sp was found to absorb CO2 better with 12.2 μmol m-2 s-1 in the herbaceous category. Whereas, Bambusa vulgaris absorbed CO2 better with 5.38 μmol m-2 s-1 in its grouping. On biomass accumulation, Alstonia scholaris has the highest aboveground accumulation of 106.94 kg followed by Samanea saman. Shrub Baphia nitida sequestered 1.06 kg, while Palm Elaesis guineensis fairly accumulated 0.09 kg biomass, whereas herbaceous plants Calathea lutea and Hymenocallis latifolia had 0.04 kg biomass accumulation as the best in their category. While, Bamboo species Phyllostachys aurea accumulated 0.05 kg as the best in its group. Result from A/Ci and AQ curve indicate that at both elevated CO2 and increase irradiance the rate of photosynthesis increase. The study identified the role of tree species in sequestering large amount of CO2 within the UTHM community. The study recommended that 274,000 trees with higher photosynthesis potential and biomass accumulation as identified in the findings of this study should be considered for planting on campus for UTHM to attain sustainability (K) from KAMI as a low carbon campus.